The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11999-012-2602-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Treatment of Intraarticular Pathology Recognized at the Time of Periacetabular Osteotomy for the Dysplastic Hip

Abstract: Level III, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…12,13 Several authors have noted symptoms after PAO that may be attributable to postoperative femoroacetabular impingement or acetabular labral tears. [13][14][15][16][17][18][19] The prevalence of intra-articular pathology at the time of PAO is substantial. 13,19,20 It stands to reason that many of these symptoms may be a cause of failure or revision surgery after osteotomy.…”
mentioning
confidence: 99%
“…12,13 Several authors have noted symptoms after PAO that may be attributable to postoperative femoroacetabular impingement or acetabular labral tears. [13][14][15][16][17][18][19] The prevalence of intra-articular pathology at the time of PAO is substantial. 13,19,20 It stands to reason that many of these symptoms may be a cause of failure or revision surgery after osteotomy.…”
mentioning
confidence: 99%
“…Labral pathologic changes were noted in 20.8%, but no specific data were provided in terms of morphologic characteristics and pattern of injury. 12 Fujii et al 10 In a larger single-center series of 73 hips treated by PAO-hip arthroscopy, Ross et al 22 reported the presence of labral tears or degeneration in 63 hips (86.3%), and the labrum was classified as hypertrophic in 46 hips (63%). The current study includes patients from that series but clearly represents a much larger, multicenter cohort from which to draw more generalizable conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…17 Through several retrospective case series, symptomatic acetabular dysplasia has also been associated with a hypertrophied labrum, labral tears, and chondral injuries. 9,10,12,16,18 The presence of a hypertrophied labrum, in particular, has been suggested by some to be a consistent diagnostic finding in acetabular dysplasia. 16 While periacetabular osteotomy may be successful to reorient the acetabulum and improve anterolateral coverage of the femoral head, adjunctive procedures are often performed to address coexisting intra-articular pathologic changes.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The transtrochanteric surgical dislocation approach, devised by Ganz et al, is now standard for nondestructive, extensive, open intra-articular hip preservation surgery around the world [40][41][42] . Newer approaches to the hip joint allow surgery to be performed directly on articular cartilage, but biological obstacles to chondral repair remain a strong incentive to correct mechanical problems before irreversible chondral damage occurs 2,13,14,43 . Experience provided by the surgical dislocation approach has facilitated the development of less invasive arthroscopic surgery to address a subset of intra-articular hip disorders that can be safely accessed through percutaneous portals 38,44 .…”
Section: Thirty Years Of Experience In Joint-preservation Surgerymentioning
confidence: 99%